Variasi Waktu Pembacaan Setelah Stop Solution Terhadap Nilai Absorbansi Anti HBS Metode Elisa - Budi - Santosa (Poltekkes Kemenkes Mataram, 2020)
Enzyme-Linked Immunosorbent Assay (ELISA) is a biochemical technique used in the field of immunology to presence detection of antibodies or antigens in a sample. After providing a stop solution, it is necessary to know the right time for the absorbance reading. The purpose of this study was to determine the anti HBs titer with absorbance reading time variation (immediate, 30 minutes and 60 minutes). This research is an experimental study. The study population was D4 Health Analyst University Student Muhammadiyah Semarang Class 2018 after hepatitis B vaccination as many as 20. To know the difference in variation during the reading, Kruskal-Wallis test was conducted. The results showed the average absorbance at an immediate reading, 30, and 60 minutes complete in complete 1,931, 1,489, 1,276. Kruskal-Wallis statistical analysis obtained a p value of 0.00. The conclusion is obtained between the variation of absorbance reading time on the ELISA method